Semi-market mathematical model of radio electronic maintenance of anti-air missile arms - Volodymyr Mirnenko; Serghij Kitik (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The paper presents a mathematical model of maintenance of electronic equipment for anti-aircraft missile weapons, which are operated according to a planned preventive operation strategy. The model is constructed using a semi-Markov random process. As a model of failures, a diffusion-nonmonotonic distribution law is used, which is typical for electronic products due to electrical phenomena, and errors of the first type are taken into account. The analytical dependence of the technical utilization coefficient on the parameters of the scale and shape of the diffusion-nonmonotonic distribution, the frequency of maintenance, the duration of the complete restoration of the equipment sample, the probability of a failure signal is established. The graphs of the dependence of the technical utilization coefficient on the indicated model parameters are given. The existence of an optimal frequency of technical maintenance is proved, at which the maximum value of the coefficient of technical use is ensured. The main results were obtained using the numerical calculation method.